Single-Cell Profiling of Epigenetic Modifiers Identifies PRDM14 as an Inducer of Cell Fate in the Mammalian Embryo - Adam Burton (Cell Reports, 2013)
Cell plasticity or potency is necessary for the formation of multiple cell types. The mechanisms underlying this plasticity are largely unknown. Preimplantation mouse embryos undergo drastic changes in cellular potency, starting with the totipotent zygote through to the formation of the pluripotent inner cell mass (ICM) and differentiated trophectoderm in the blastocyst. Here, we set out to identify and functionally characterize chromatin modifiers that define the transitions of potency and cell fate in the mouse embryo. Using a quantitative microfluidics approach in single cells, we show that developmental transitions are marked by distinctive combinatorial profiles of epigenetic modifiers. Pluripotent cells of the ICM are distinct from their differentiated trophectoderm counterparts. We show that PRDM14 is heterogeneously expressed in 4-cell-stage embryos. Forced expression of PRDM14 at the 2-cell stage leads to increased H3R26me2 and can induce a pluripotent ICM fate. Our results shed light on the epigenetic networks that govern cellular potency and identity in vivo.